Pemberdayaan Masyarakat dan Pengembangan Kapasitas dalam Penanggulangan Kemiskinan melalui PNPM Mandiri Perkotaan - Bambang Sugeng Dwiyanto; Jemadi Jemadi (Universitas Proklamasi 45 Yogyakarta, 2013)
Community empowerment is an attempt to make people become empowered through learning efforts so that they are able to manage and be responsible for development programs in the community. Learning is implemented in a series of community development. The purpose of this research was to evaluate the process of community empowerment in PNPM Urban activities in terms of aspects Sastrodirjan village community development, with the goal of research is to assess the implementation of community development, assessing public attitudes and perspectives on community empowerment and assess the degree of empowerment. The approach in this research is deductive method of qualitative analysis and quantitative descriptive . Results reveal that the capacity of community development activities in the village Sastrodirjan has been implemented in accordance with the principles of empowerment and have managed to change the level of public awareness and increase understanding of the role of development in their communities. The findings obtained are changes in public awareness of the respondents did not relate to age, level of education and its role in PNPM, but having a relationship with sex, where the role and involvement of women is still low and not enough to support optimal development at the community level.